2007
DOI: 10.1590/s0102-86502007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the effects of a polypropylene prosthesis on testicular volume and arterial flow in patients undergoing surgical correction for inguinal hernia

Abstract: Purpose:To evaluate testicular volume and arterial flow in patients undergoing surgical correction for inguinal hernia, with polypropylene prosthesis. Methods: This was an observational prospective clinical study on 39 male patients with unilateral inguinal hernia of types III A and III B according to the Nyhus classification who underwent surgical correction with implantation of a polypropylene prosthesis by means of the Lichtenstein technique. The patients were evaluated using Doppler ultrasound before the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Neto et al ., Ramadan et al ., and Lal et al . did not find any statistically noteworthy elevation in RIs, which is in conjugation with our study[ 18 19 20 ] where no significant difference between the RI of any artery in their preoperative and early postoperative period was noted. Roos et al .…”
Section: Discussionsupporting
confidence: 89%
“…Neto et al ., Ramadan et al ., and Lal et al . did not find any statistically noteworthy elevation in RIs, which is in conjugation with our study[ 18 19 20 ] where no significant difference between the RI of any artery in their preoperative and early postoperative period was noted. Roos et al .…”
Section: Discussionsupporting
confidence: 89%
“…Studies by Beddy et al [4] and EI-Awady et al [5] have shown that the resistive index on the side of a unilateral hernia is significantly higher than that on the normal side. On the other hand, Neto et al [6] and Ramadan et al [7] did not observe any statistically significant elevation in resistive indexes. In this study, we conducted a comparison of testicular temperature, volume, and blood perfusion before surgery on both the inguinal hernia side and the healthy side.…”
Section: Discussionmentioning
confidence: 85%
“…As a result; there are many clinical and experimental study results in which has advers effect or not on testicular perfusion (Lima Neto et al 2007; Koksal et al 2010). We thougt that it is difficult to impair the testicular perfusion after hernia repair, because of it has rich arterial supplay and collateral capacity.…”
Section: Discussionmentioning
confidence: 99%